PENANGANAN LIMBAH MEDIS DAN PERILAKU PETUGAS CLEANING SERVICE DI RSUD Dr. SOETOMO SURABAYA TAHUN 2016 - Risca Anesea; Erna Triastuti; Ferry Kriswandana (GEMA LINGKUNGAN KESEHATAN, 2016)
Health workers who handle medical waste are at risk of the diseases faced because of germs from the skin infections, anthrax, meningitis, dengue, hepatitis A, Hepatitis B and C. The bacteria present in the blood are transmitted through blood. The highest risk of being infected by these diseases is when impaled by sharp or pointed object of the waste because it can damage the skin. The purpose of this study was to determine the behavior of CS officers (Cleaning Service) and the handling of medical waste in Dr. Soetomo hospital. This is a descriptive research with cross sectional approach. The collection of data was carried out through observation and interviews. The sample was 75 CS officers. Data were analyzed descriptively with table analysis.The results showed that Cleaning Services’ level of knowledge at Dr. Soetomo Hospital on handling medical waste with "Good" criteria was 90.8%. The CS attitude with "good" criteria was 88% and poor was 5.3%. CS’s behavior with "Good" criteria was 92% and "poor" was 6.7%. It can be concluded that of 75 Cleaning Service at Hospital Dr. Soetomo, most of them were well behaved and only a small proportion have poor behavior. The handling of medical waste in Dr. Soetomo hospital has been qualified in accordance with Kepmenkes No 1204 of 2004. It is recommended to conduct counseling on the importance of the use of personal protective equipment and the dangers of medical waste. Warning is also needed to officers whose work is not according to the rules. Keywords: CS Behavior, handling of medical waste